How do Climate Shocks Affect the Impact of FDI, ODA and Remittances on Economic Growth? - Drabo, Alassane (IMF Working Papers; Working Paper ;, 2021)
The three main financial inflows to developing countries have largely increased during the last two decades, despite the large debate in the literature regarding their effects on economic growth which is not yet clear-cut. An emerging literature investigates the dependence of their effects on some country characteristics such as human and physical capital constraint, macroeconomic policy and institutional capacity. This paper extends the literature by arguing that climate shocks may undermine the effect of Foreign Direct Investment (FDI), official development assistance (ODA) and migrants' remittances on economic expansion. Based on neoclassical growth framework, the theoretical model indicates that FDI, ODA, and remittances improve economic growth, and the size of the effect increases with good absorptive capacity. However, climate shocks reduce this positive effect of financial flows in developing countries. Using a sample of low and middle-income countries from 1995 to 2018, the empirical investigation confirms the theoretical conclusions. Developing countries should build strong resilience to climate change. Actions are also needed at global level to reduce greenhouse gases emissions, and build strong structural resilience to climate shocks especially in developing countries.